Social ties and negotiation of lexical norms in Old English: The vocabularies of vices - Olga Timofeeva; Christine Wallis (Lexis: Journal in English Lexicology)
This paper aims to document the coinage and diffusion of sin-lexemes and to evaluate the extent of their regional, chronological, and social reach. It starts by tracing the genesis of these concepts and lexemes in Latin and Old English texts, with a particular focus on their usage during the Benedictine reforms in the second half of the tenth century. Special attention is given to the works of Ælfric of Eynsham (c. 950-1010) and Archbishop Wulfstan (d. 1023), who are known to have collaborated on texts for religious instruction. In addition, the paper examines evidence from anonymous treatises such as the Capitula Theodulfi (c. 800, translated into English around the time of Ælfric and Wulfstan), as well as the works of Byrhtferth of Ramsey (c. 970-1020) and penitential literature. Despite the strong link between Ælfric and Wulfstan, comparisons with other contemporary authors, and especially penitentials, reveal that Ælfrician vocabulary did not achieve widespread adoption. This lack of uniformity may have contributed to the limited survival of Old English sin-lexemes into the Middle English period.